A Family of Human MicroRNA Genes from Miniature Inverted-Repeat Transposable Elements - Piriyapongsa, Jittima (Public Library of Science, 2007)
While hundreds of novel microRNA (miRNA) genes have been discovered in the last few years alone, the origin and evolution of these non-coding regulatory sequences remain largely obscure. In this report, we demonstrate that members of a recently discovered family of human miRNA genes, hsa-mir-548, are derived from Made1 transposable elements. Made1 elements are short miniature inverted-repeat transposable elements (MITEs), which consist of two 37 base pair (bp) terminal inverted repeats that flank 6 bp of internal sequence. Thus, Made1 elements are nearly perfect palindromes, and when expressed as RNA they form highly stable hairpin loops. Apparently, these Made1-related structures are recognized by the RNA interference enzymatic machinery and processed to form 22 bp mature miRNA sequences. Consistent with their origin from MITEs, hsa-mir-548 genes are primate-specific and have many potential paralogs in the human genome. There are more than 3,500 putative hsa-mir-548 target genes; analysis of their expression profiles and functional affinities suggests cancer-related regulatory roles for hsa-mir-548. Taken together, the characteristics of Made1 elements, and MITEs in general, point to a specific mechanism for the generation of numerous small regulatory RNAs and target sites throughout the genome. The evolutionary lineage-specific nature of MITEs could also provide for the generation of novel regulatory phenotypes related to species diversification. Finally, we propose that MITEs may represent an evolutionary link between siRNAs and miRNAs.